Colorimetric Solvent Indicators Based on Nafion Membranes Incorporating Nickel(II)‐Chelate Complexes. Issue 46 (13th October 2014) - Hosokawa, Hitoshi; Funasako, Yusuke; Mochida, Tomoyuki
Abstract To develop solvent‐recognition films, Nafion membranes incorporating cationic nickel‐chelate complexes, that is, [Ni(L1)(L2)]+ (HL1=acetylacetone, 2, 2, 6, 6‐tetramethyl‐3, 5‐heptanedione; L2=N, N‐diethylethylenediamine, N‐butyl‐N, N′, N′‐trimethylethylenediamine), were prepared. Immersion of the films in various solvents effected the color changes varying from red to pale blue green depending on the donor number of the solvents. The color change is based on an equilibrium shift between square‐planar and solvent‐coordinated octahedral geometries of the cations. The degree of the color change depended on the affinity of the incorporated complex to the solvent molecules. The films were robust and exhibited a reversible solvent response. The films exhibited thermochromism when a small amount of appropriate solvents were incorporated and changed from pale blue green at low temperatures to red at high temperatures.